English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2/x-1 = 4 - x/x-1

In other words:
**2 over x-1 = 4 minus x over x-1**

2007-01-27 12:41:45 · 3 answers · asked by Anonymous in Science & Mathematics Mathematics

3 answers

multiply by (x-1)
2 = 4(x-1) -x
2 = 4x -4 -x = 3x - 4
3x = 6
x=2

2007-01-27 12:47:25 · answer #1 · answered by really? 2 · 0 0

To solve (2/(x-1))=((4-x)/(x-1)) multiply both sides of the equation by (x-1)/1. This should give you (2(x-1))=((4-x)(x-1)). Now you can solve this equation by getting the x on one side of the equation and simpifying. Let me know if you need more help.

2007-01-27 12:50:32 · answer #2 · answered by Steve 1 · 0 0

2/2-1=4-2/2-1=0

X=2

2007-01-27 12:46:59 · answer #3 · answered by Truth D 4 · 0 0

fedest.com, questions and answers